An investigation of the role of digital libraries in bridging the digital divide in developing Arab countries: the case of Yarmouk University, Jordan - Obeidat, Othman (Curtin University, 2009)
Developing countries are often said to suffer the disadvantages created by a ‘digital divide’ – the gap between the digitally advantaged and the digitally disadvantaged. This study examines the phenomenon of the digital divide in the context of Jordan as an example of a developing Arab country. The research question for the study is: How can digital libraries assist universities in Jordan to bridge the digital divide?This research question is addressed by using the established method of a document availability test to measure the availability of randomly selected documents at Yarmouk University, Jordan; and conducting a comparison with Curtin University as an example of an established university in a developed country. This test serves as the basis for a survey and interviews undertaken with academic and library staff from Yarmouk University, and senior government policy makers in Jordan.A focus of the study is on assessing the particular challenges and frustrations facing Arabic-speaking researchers in their use of digital information services. That is, while the term digital divide is often used as a means of expressing the technology gap between developed and developing countries, it may well be that a further divide is created because of the domination of the languages and content of the developed world in the digital environment.The findings of the research make recommendations regarding the digital scholarly environment in Jordan. These include the need to: 1. develop a more mature research culture, 2. enhance professionalism and skill development in academic library staff, 3. increase collaboration in the creation and delivery of digital scholarly content, 4. develop open access publishing and archives, 5. improve advocacy and training roles of academic librarians.